Poultry litter and cow dung biochar as P sources for cowpea cultivation in two Ghanaian soils - Nartey, Eric K.; Sulemana, Nasirudeen; Razak, Awudu; Adjadeh, Thomas A.; Akumah, Asiwome M.; Amoatey, Christiana; Abekoe, Mark K. (Frontiers in Agronomy, 2023)
The main constraint to cCowpea, Vigna unguiculata [L. Walp] is an important annual herbaceous legume whose production in West Africa is affected by the unavailability of applied phosphorus due to ligand exchange with clay minerals and precipitation reactionsby clay minerals facilitated byand low pH and low organic matter, respectively. To overcome this challenge, cow dung biochar (CB) and poultry litter biochar (PB) were applied as P sources of P for cowpea cultivationto cowpea in a Pplinthustult and a Kkandiustalf in Ghana. The two biochar types and triple super phosphate (TSP) were applied to meet the standard phosphorus requirement (SPR) and ½ SPR of the two soils. , with Bsupplemental basal K (derived from the average K content in the two biochar types) from muriate of potashKCl was added to the TSP treatmentlatter. In addition to a non-amended soilcontrol, the treatments were triplicated and arranged in a completely randomized design (CRD) in a screen house for an efficacy trial using cowpea as the test crop. Moisture content was maintained at 80% field capacity. Hundred cowpea seed weight was 20.3 g and 19.6 g for the TSP amended Plinthustult at SPR and ½ SPR, respectively. This increased to 25.1 g and approximately 27 g at SPR and ½ SPR in the CB and PB amended Plinthustult, respectively. Hundred seed weight for TSP at both rates was similar in the two soils. The PB amended Kandiustalf at SPR had seed with a weight of 27.02 g, 1.1 g heavier than the ½ SPR. The CB amended Kandiustalf at both rates had 100 seeds weighing 25 g. Residual available P was 334.2 mg/kg and 213.2 mg/kg at SPR and ½ SPR, respectively, in the Plinthustult as opposed to a paltry 2.5 mg/kg at SPR in the TSP counterpart. The study recommends for the two biochar types to be applied at ½ SPR. Biochar amended soils at ½ SPR and full SPR for both soils induced better growth parameters than TSP and control. The plintustult performed better than the kandiustalf in all parameters measured.